Changes in bicycling frequency in children and adults after bicycle skills training: A scoping review. (May 2019) - Sersli, Stephanie; DeVries, Danielle; Gislason, Maya; Scott, Nicholas; Winters, Meghan
Highlights: Bicycle skills training is positively associated with bicycling frequency in 10 of 12 studies. More rigorous evaluations of bicycle skills training from diverse settings are needed. Theory, context, and content may help understand why outcomes vary by place and population. Context might include description of policy, infrastructure, and social milieu. Abstract: Background: Encouraging more trips by bicycle is often an objective of bicycle skills training. Bicycle skills training programs have been implemented in several countries, cities, and schools, but few evaluations measure changes in bicycling. We conducted a scoping review to identify and describe evidence of changes in bicycling frequency associated with bicycle skills training. We also describe and compare the theoretical basis, context, and training content of bicycle skills trainings that might be associated with changes in bicycling. Methods: We searched six electronic databases, grey literature websites, Google Scholar, and citations in relevant articles for pre- and post-test studies of bicycle skill training interventions which measured bicycling frequency in children or adults. We assessed the theory, context, and content of the bicycle skills training interventions using pre-defined concepts and a behaviour change technique taxonomy. Results: We found 12 studies. Six studies assessed programs for adult populations, of which five reported increases in overall bicycling and three reported increases in bicycling to work. Six studies assessed programs for children, of which five reported increases in overall bicycling and three reported increases in bicycling to school. Information about the statistical significance of these results was sometimes missing. Studies described intervention content adequately, but poorly reported details about intervention theory and context. No associations were found between intervention content and changes in bicycling frequency. Conclusions: Bicycle skills training increases participants' bicycling, but evidence is heterogeneous among a small number of studies. Sparse reporting limited our ability to detect associations between changes in bicycling frequency and the training theory, context, or content. Future studies should strive to report details on theory, context, and content to help assess effectiveness and generalizability.